Self-efficacy and performance feedback: Impacts on cognitive load during creative thinking. (February 2021) - Redifer, Jenni L.; Bae, Christine L.; Zhao, Qin
Abstract: Creative thinking is the ability to produce responses that are both original and useful. Like other complex thinking processes, creative thinking draws on higher-order cognitive resources. The impacts of feedback, cognitive load, and self-efficacy on traditional complex thinking activities are well documented; however, little is known about how these factors influence creative thinking, which is unique in its requirement of originality. We investigated the impacts of social comparison performance feedback and creative self-efficacy on cognitive load during two creative thinking (divergent thinking) tasks. Higher creative self-efficacy was associated with lower cognitive load during creative thinking. Positive feedback was associated with lower cognitive load compared to negative feedback. Higher cognitive load negatively impacted creative thinking performance, and the impacts of creative self-efficacy and performance feedback on creative thinking were partially mediated by cognitive load. Implications for providing feedback to students during creative thinking tasks are discussed. Highlights: Social comparison feedback about creative thinking performance was provided. High self-efficacy led to lower cognitive load than low self-efficacy. Negative feedback led to higher cognitive load than positive feedback. Higher cognitive load led to worse creative thinking performance. Impacts of self-efficacy and feedback were partially mediated by cognitive load.